Endogenous salicylic acid potentiates cadmium-induced oxidative stress in Arabidopsis thaliana - Zawoznik, Myriam Sara (2007)
To better understand the role of endogenous salicylic acid (SA) in plants exposed to abiotic stresses known to generate oxidative damage, the response to cadmium treatment of a wild Arabidopsis thaliana ecotype and a SA-deficient transgenic line was investigated. After 5 days of Cd treatment, chlorophyll content was significantly reduced and TBARS significantly increased in wild type seedlings but not in the SA-deficient line. Leaves of wild type plants exposed to the metal showed accumulation of H2O2 and increased oxidized glutathione content, resulting in decreased GSH/GSSG ratios. After Cd treatment, transgenic plants displayed a significantly decreased SOD activity (about 50% of control) which may have contributed to prevent H2O2 increase. The activity of several H2O2-detoxyfing enzymes diminished in wild type seedlings exposed to the metal (27–35% decrease). In SA-deficient plants ascorbate peroxidase and glutathione peroxidase activities slightly decreased, but guaiacol peroxidase and catalase activities significantly increased. CAT1 isoform was found to be particularly abundant in wild type Arabidopsis plants exposed to Cd, but scarcely expressed and almost unaffected by the metal addition in the transgenic line. Even when protective effects of SA have been extensively reported for several plant species, our results suggest that endogenous SA may function in A. thaliana as a signaling molecule necessary to generate, to sustain or to amplify Cd-induced oxidative stress.